PERKEMBANGAN KESENIAN SEKURA DI WILAYAH SKALA BRAK PAKSI BUAY PERNONG KABUPATEN LAMPUNG BARAT TAHUN 1991-2017 - Sheptia Lea Maharani, - (2022)
Abstract This research is titled "Development of Sekura Art in Brak Paksi Buay Pernong Scale Area of West Lampung Regency in 1991-2017". This research is based on significant changes that occur in Sekura art from year to year. The problem studied by researchers is how the changes and development of Sekura art in the buay pernong kingdom that started from how sekura began to emerge, what changes happened to Sekura art, sekura's shifting values and functions, and conservation efforts made by indigenous leaders, communities, and governments. The problem researchers studied using historical methods, namely heuristics, criticism, interpretation, and historiography. Based on the results of this thesis research can be known that the background of the emergence of art Sekura condition of the muslim community who want the celebration of Eid al-Fitr celebrated with local culture as a sign of victory after running 30 days of fasting. The then resemi was used as regional art in 1991 where Sekura was first paraded in the framework of the separation of West Lampung which formed its own regency. Since then Sekura continued to be on display until it experienced several changes in function that were originally only paraded to celebrate the day of victory, then turned into a matchmaking event, a race event of each region. The ups and downs of Sekura art continued to occur in the early 2000s Sekura began to be abandoned but the government's efforts in 2014 and 2016 held a sekura 1000 face and managed to break the muri record managed to attract the attention and interest of the public to re-hold sekura art that had receded. Since then all communities and indigenous leaders have been trying to preserve Sekura like the traditional figures who made sekura dances that were introduced at national festivals. Abstrak Penelitian ini berjudul "Perkembangan Kesenian Sekura di Wilayah Skala Brak Paksi Buay Pernong Kabupaten Lampung Barat Tahun 1991-2017". Penelitian ini dilatar belakang dengan adanya perubahan signifikan yang terjadi pada kesenian Sekura setiap tahunya. Permasalahan yang dikaji peneliti adalah bagaimana perubahan dan perkembangan kesenian Sekura di wilayah kerajaan Buay Pernong yang dimulai dari bagaimana awal kemunculan Sekura,peralihan nilai dan fungsi Sekura, dan upaya pelestarian yang dilakukan seluruh masyarakatnya. Permasalahan tersebut peneliti kaji menggunakan metode historis yaitu heuristik, kritik, interpretasi, dan historiografi. Berdasarkan hasil penelitian skripsi ini dapat diketahui bahwa yang latarbelakangi kemunculan kesenian Sekura kondisi masyarakat yang beragama islam yang menginginkan perayaan hari raya idul fitri dirayakan dengan kebudayaan lokal sebagai tanda kemenangan setelah menjalankan 30 hari puasa. Yang kemudian resemi dijadikan sebagai kesenian daerah pada tahun 1991 dimana Sekura pertama kali dipawaikan dalam rangka pemisahan Lampung Barat yang membentuk Kabupaten sendiri. Sejak saat itu Sekura terus di pertontonkan hingga mengalami beberapa kali perubahan fungsi yang semula hanya dipawaikan saja untuk merayakan hari kemenangan, kemudian beralih menjadi ajang pencarian jodoh, ajang perlombaan setiap daerah. Pasang surut kesenian Sekura terus terjadi di awal tahun 2000an Sekura mulai ditinggalkan namun upaya pemerintah pada tahun 2014 dan 2016 mengadakan sekura 1000 wajah dan berhasil memecahkan rekor muri berhasil menarik perhatian dan minat masyarakat untuk kembali mengadakan kesenian Sekura yang sempat surut. Sejak saat itu seluruh masyarakat dan tokoh adat berupaya terus melestarikan Sekura seperti tokoh adat yang membuat tarian Sekura yang dikenalkan di festival nasional.